Massive open online course (MOOC) with learning objects and intelligent agent technologies - Goh, Ong Sing; Abd Ghani, Mohd Khanapi; Jaya Kumar, Yogan; Choo, Yun Huoy; Draman @ Muda, Azah Kamilah (2014)
The use of e-learning and m-learning is increasing in both academic and industrial training contexts especially on the implementation of the Massive Open Online Course (MOOC). The challenge today for educators is how to design and develop educational software using Learning Object and Intelligent Agent Technologies to increase the users’ participation and engagement with the course materials that are offered. This paper aims to sharing the authors’ experiences with the development of an edutainment system, which comprised of the embodied conversational agent and learning objects.